The understanding of the nature of science by science teachers and nonscience teachers a comparative study - Almazan, Rosemary R. 1946- (s.n.], 1972)
The Test on Understanding Science (TOUS) Form W was administered to forty science high school teachers, forty nonscience high school teachers, forty elementary school nonscience teachers, and forty elementary nonscience teachers. The t-test for difference of means was applied to the scores of the four groups of teachers on the total test on three major areas covered by the test: (a) the scientific enterprise, (b) the scientist, and (c) the methods and aims of science.